Circulating extracellular vesicles from severe COVID-19 patients induce lung inflammation - Huifeng Qian; Ruoxi Zang; Ruoyang Zhang; Guoping Zheng; Guanguan Qiu; Jianbiao Meng; Jiangmei Wang; Jie Xia; Ruoqiong Huang; Zhenkai Le; Qiang Shu; Jianguo Xu (mSphere)
ABSTRACT Circulating extracellular vesicles (EVs) have been associated with the development of COVID-19 due to their roles in viral infection, inflammatory response, and thrombosis. However, the direct induction of lung inflammation by circulating EVs from severe COVID-19 patients remains unknown. EVs were extracted from the plasma of severe COVID-19 patients admitted to intensive care and healthy controls. To study the effect of COVID-19 EVs on lung inflammation, mice were intratracheally instilled with EVs. To examine the proinflammatory effects of EVs in vitro, bone marrow-derived macrophages were treated with EVs. COVID-19 but not control EVs triggered lung inflammation, as assessed by total protein level, total cell count, neutrophil count, and levels of proinflammatory cytokines in the bronchoalveolar lavage. COVID-19 EVs also promoted M1 polarization of alveolar macrophages in vivo. Treatment of bone marrow-derived macrophages with COVID-19 EVs enhanced the M1 phenotype and augmented the production of IL-1β, IL-6, and TNF-α. In summary, circulating EVs from severe COVID-19 patients induce lung inflammation in mice. EVs could become a potential therapeutic target for alleviating lung injury in COVID-19.IMPORTANCEExtracellular vesicles (EVs) have been reported to facilitate cytokine storm, coagulation, vascular dysfunction, and the spread of the virus in COVID-19. The direct role of circulating EVs from severe COVID-19 patients in lung injury remains unrecognized. Our study demonstrated that plasma EVs obtained from severe COVID-19 patients induced lung inflammation and polarization of alveolar macrophages in vivo. In vitro experiments also revealed the proinflammatory effects of COVID-19 EVs. The present study sheds fresh insight into the mechanisms of COVID-19-induced lung injury, highlighting EVs as a potential therapeutic target in combating the disease.